Per Rectal Magnetic Infra- Red Laser Therapy (Milt) by Optical Probe and Haematospermia With Chronic Pelvic Pain Syndrome (Cpps) / Chronic Prostatitis - Choudhury, Abdul Matin Anamur Rashid; Parveen, Tasmina (Bangladesh Journal of Urology, 2020)
Objective : To observe improvement of symptoms of haematospermia after treatment with Magnetic infra-red laser therapy (MIL-therapy) in patients ofhaematospermia with Chronic Prostatitis. Method: Observational study was done on 30 male patients with haematospermiawith CPPS or Chronic prostatitis , age range varied from30 to 60 years. The study was conducted from 2004 to 2008 in a private medical center in Dhaka city.The MIL therapy in use has a wave length of 1000Hz. The Laser beam reaches the prostate and seminal vesical with a special optic probe. In this study the prostate anad seminal vesicle was examined per rectally by doing digital rectal examination with use of gloves and gel .The treatment schedule was one treatment every two days ( treatment time of 5 to 10 minutes ,wave length 1000Hz) for a total 10 application . After 10 application patients were asked for follow-up and data were collected and analysed. Result :Among 30 patients of Haematospermia with Chronic prostatitis aged between 30-60 years with complains of blood discharge in semen were under treatment with MIL therapy . 25 patients with haematospermia were cured and 04 patients improved after laser treatment . But 01 patient found not improved on patients history. Conclusion : Complains of patients and sign -symptoms cured and improved after MIL therapy. Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.170-176